Correlation between miR-146a and miR-155 levels and concentration of cytokines in patients with allergopathy in chronic persistence of Epstein-Barr virus infection - S. Zubchenko; G. Potemkina; V. Chopyak; K. Lishchuk-Yakymovych (Journal of Education, Health and Sport, 2019)
Analysis of correlation between miR-146a and miR-155 levels and concentration of antiviral cytokines in patients with allergopathy in active and latent phases of chronic persistence of Epstein-Barr virus infection (EBV) has been conducted. Thus, 38 patients with allergopathy and chronic persistence of EBV of different genders, age 32.73.2 years have been examined, who were divided into groups depending on the phases of virus persistence. Control group included 20 healthy individuals. Reliable changes in IL12, IL33, IL1ß and IFN- were revealed in patients of both groups. The results: reliably higher levels of miR-146a expression, by 2.9 times (р=8.0E-04) and by 2.25 times (р=0.011), respectively, compared with control group; reliable difference in miR-155 levels in patients with EBV-infection in active and latent forms of virus persistence (р=1.0E-07) and significant decrease in the indicated miRNA (р=1.0E-07) by 55.8 times in patients with latent course of EBV-infection compared with control. A reliable reverse correlation of various intensities was detected between IL12, IL1ß, IFN- and miR-146a; absence of correlation between TNF-α, IL33 and miR-146a was observed. A direct correlation was revealed between all investigated cytokines IL12, TNF-α, IL33, IL1ß, IFN- and miR-155. the results of investigation showed that elevation of miR-146a can prognostically indicate inhibition of pro-inflammatory activity of cytokines and anti-inflammatory protection with the formation of pathological disorders, including allergopathy. Meanwhile, the presence of chronic persistence of EBV demonstrates an opposite direction of correlations between miR-155 and cytokines with pro-inflammatory properties, which confirms the ability of opportunistic infections to modulate immune response toward allergopathy.